The WorId Bank's information sources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The World Bank is better known as a financial institution than as a source of information about development but, each year, it produces over 400 publications and many hundreds of economic, sectoral and evaluation reports. It issues over a hundred...